Proceedings of the 7th International Conference on Communities and Technologies 2015
DOI: 10.1145/2768545.2768559
|View full text |Cite
|
Sign up to set email alerts
|

Understanding future challenges for networked public display systems in community settings

Abstract: Networked public displays are envisioned as a communication medium for the 21 st century, and as such they have a great potential to address place-based communities. This area has seen an increasing numbers of investigations of networked public displays effects on communities and the way they impact interactions between community members. However, most of this research stands alone in isolation, with little work looking into synthesizing the systems, processes, research questions, and evaluation procedures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This, together with the constant flow of new residents and tourists, provides us with a unique chance to explore the displays' discoverability, usability factors, and learnability, and the perceived longterm relevance of the displays as well as their content. While several open challenges remain, 15 the challenges we have identified here are an important starting point for strengthening the long-term potential of public displays and their sustained, meaningful use.…”
Section: Designing For the Long Termmentioning
confidence: 97%
See 1 more Smart Citation
“…This, together with the constant flow of new residents and tourists, provides us with a unique chance to explore the displays' discoverability, usability factors, and learnability, and the perceived longterm relevance of the displays as well as their content. While several open challenges remain, 15 the challenges we have identified here are an important starting point for strengthening the long-term potential of public displays and their sustained, meaningful use.…”
Section: Designing For the Long Termmentioning
confidence: 97%
“…Finding and Using applications One of the most promising purposes for public displays is community engagement. 15 While the majority of past public display research projects has focused on a single application deployed on a single display, or a set of displays, there exist several motives for public displays to be multipurpose. 1,7 For example, such displays can implement various monetization models and host several types of applications in an attempt to offer "something for everyone."…”
Section: Pervasive Displaysmentioning
confidence: 99%
“…To date, some scholars have argued that there may be cultural differences between designers and local user communities (Sabiescu et al 2014;Winschiers-Theophilus et al 2015). Studies on longterm multi-stakeholder projects have also pointed out a number of challenges (Cheverst et al 2012;Clinch et al 2011;Dalsgaard andHalskov 2010, Friday et al 2012;Halkola et al 2015;Memarovic 2015;Ståhlbröst et al 2015;Taylor et al 2013;Ylipulli and Suopajärvi 2013), while cultural analyses of such projects are limited. This study contributes by showing that not only designers and users or user communities with their (cultural) values shape the process, but that there is an even greater versatility of stakeholders and their (cultural) values and technology requirements and interpretations, which may further complicate the picture.…”
Section: Cultural Values Stakeholder Requirements and User Interprementioning
confidence: 99%
“…However, cultural analyses of long-term multi-stakeholder technology design projects are rare. Some studies addressing these projects came close, for example, by addressing the intricacies and challenges of collaboration (e.g., Halkola et al 2015;Sabiescu et al 2014;Ståhlbröst et al 2015;Winschiers-Theophilus et al 2015) that have also been studied in ubiquitous computing and public display projects (Cheverst et al 2012;Clinch et al 2011;Dalsgaard and Halskov 2010;Friday et al 2012;Memarovic 2015;Memarovic et al 2013;Suopajärvi et al 2012;Taylor et al 2013;Taylor and Cheverst 2009;Taylor and Cheverst 2010;Ylipulli and Suopajärvi 2013). Some studies addressed cultural aspects of developing country or community technology design contexts, within which it has been shown that local cultural aspects must be taken seriously by the designers who represent another culture (Sabiescu et al 2014;Winschiers-Theophilus et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The dichotomy between mobile and LBS (location-based services) is resolved with "mobileambient" transmedial interfaces that exploit both individual mobile devices and shared locative public media. Twhirleds' mobile affordances projected onto social screens with back-projection of virtual camera position instantiate integration of telemetric personal control and public display (Memarovic 2015). Mixed reality and virtuality environments, using fluid perspective to blur the distinction between sampled and synthesized data, are literally illuminated by networked lighting.…”
Section: Fig 20mentioning
confidence: 99%